UPAYA MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR SISWA PELAJARAN PENDIDIKAN AGAMA ISLAM - Asep Halimurosid (ADIBA : JOURNAL OF EDUCATION, 2023)
This study aims to determine efforts to increase learning achievement and learning motivation of 6th grade students at SDN Hegarmanah Cugenang Cianjur through the experimental test method in the Islamic Religious Education Curriculum, which consists of two cycles, Cycle I and Cycle II. The research object was 38 students in the class, and the research object was learning achievement and learning motivation. The test equipment used is in the form of student learning achievement tests to measure student learning motivation and learning achievement tests to measure learning achievement in cycles I and II. The data collected is in the form of quantitative data. Data analysis method is descriptive and quantitative. The results showed that the initial reflection data on average academic achievement and canon integrity were relatively suboptimal in terms of knowledge and skills in Islamic religious education courses, but after the first cycle, the results increased along with the average academic achievement. 75. The learning completeness level reaches 75%, and the average result of observing students' learning motivation reaches 65%. After the implementation of cycle II as a whole, the average score increased by 81%, and the completeness level was 94% higher than the results of the initial reflection. Meanwhile, overall learning motivation increased by 29% in cycles I and II to complete learning outcomes. The conclusion is that the test-experimental method can increase intrinsic motivation in encouraging someone to come purely from within the student and can increase students' motivation to learn PAI in grade VI. 2) Experimental learning of growing tests can increase intrinsic motivation tends to encourage people to be stronger, and the achievement is more satisfying. It can improve Islamic learning outcomes for grade VI students.